Nitrogen-oxygen co-doped carbon material as well as preparation method and application thereof
Through the preparation method of nitrogen and oxygen co-doped carbon materials, the problem of low yield of carbon material reinforcement agents is solved, high yield and stability are achieved, and further market demand for rubber reinforcement properties is met.
Patent Information
- Application Number
- CN202510037855.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Existing carbon material reinforcement agents have problems with low yields or unstable yields, and the market demand for the performance of rubber reinforcement agents has further increased.
Using nitrogen and oxygen co-doped carbon materials and their preparation method, potassium aspartate, aminophyline and hydrophilic polymer are dissolved in deionized water, heated and stirred, and mixed with crosslinking agent, and lyophilized. Treatment to produce nitrogen and oxygen co-doped carbon material.
The yield of carbon material reinforcement agent is improved, with a yield up to 32%, and the yield is stable, and the yield remains above 29%, which significantly improves the performance of rubber products.
Smart Images

Figure CN119430154A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon materials, and in particular, relates to a nitrogen-oxygen co-doped carbon material and a preparation method and application thereof. Background Art
[0002] Rubber is a widely used industrial product. In order to meet the different requirements of rubber products in various fields, many additives with different functions are usually added during production to improve the mechanical properties of rubber such as tensile strength, wear resistance, tear strength, and tensile stress, improve the performance, and extend the service life of the product. This effect is called rubber reinforcement, and these substances are called reinforcing agents. Carbon is one of the most common elements in nature. The bonding between atoms is diverse and it is easy to form allotropes with very different structures and properties. From traditional carbon black to the latest two-dimensional graphene, carbon materials have always had an irreplaceable position and role in the field of materials science with their unique and excellent physical, electrical and thermal properties. Carbon materials as rubber reinforcing fillers can enhance its physical, thermal, electrical and gas / liquid barrier properties and reduce the production cost of rubber products. However, at present, the yield of common carbon material reinforcing agents is low, resulting in high production costs and low production capacity, affecting production cycles and production volumes.
[0003] In the field of rubber reinforcement agents, the inventor and his team have conducted a lot of research. For example, patent CN118954485A discloses a preparation method and application of oxygen-sulfur doped porous carbon materials for rubber waterstop reinforcement agents, which converts inert elemental sulfur into active sulfur sites dispersed on polyvinyl chloride, improves the performance of rubber products, and reduces the amount of sulfur used in the preparation of rubber waterstops; patent CN116986584A relates to a preparation method of nitrogen-phosphorus-iron doped carbon materials and their application in rubber, and the prepared carbon materials can effectively reinforce rubber; patent CN116332157B relates to a preparation method of nitrogen-metal doped carbon materials and their application in rubber, and the prepared carbon materials can effectively reinforce rubber; but currently, carbon material reinforcement agents still have the problems of low yield or unstable yield, as well as the market's further demand for the performance of rubber reinforcement agents.
[0004] Therefore, providing a carbon material reinforcing agent with stable yield, good performance, safety and high yield has important practical significance and broad market value. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a nitrogen-oxygen co-doped carbon material and a preparation method and application thereof.
[0006] To solve the above problems, the technical solution adopted by the present invention is: Technical theme 1: The present invention provides a nitrogen-oxygen co-doped carbon material, and the preparation method is as follows: S1: dissolving potassium aspartate, aminophylline and a hydrophilic polymer in deionized water, heating and stirring to obtain an emulsion A; S2: dissolving the cross-linking agent in methanol, heating and stirring to obtain solution B; S3: heating and stirring solution B, while adding emulsion A dropwise into solution B, and continuing heating and stirring after the addition is complete to obtain an intermediate product; S4: freeze-drying the obtained intermediate product and then calcining it to obtain a nitrogen-oxygen co-doped carbon material; The hydrophilic polymer includes crotonamide, maleamic acid, acrylamide or propionamide; The cross-linking agent includes triethylene glycol dimethacrylate, polyethylene glycol diacrylate or methoxy polyethylene glycol acrylate.
[0007] Furthermore, the mass ratio of potassium aspartate, aminophylline, hydrophilic polymer and cross-linking agent is 6~10:2~4:3~8:1.4~2.
[0008] Furthermore, the ratio of the cross-linking agent to methanol is 1 g: 5-15 mL.
[0009] Furthermore, the volume ratio of the emulsion A to the solution B is 2.5-3.5:1.
[0010] Furthermore, the heating and stirring temperature is 35-45° C.; the heating and stirring time in S1 is 30-50 min; the heating and stirring time in S2 is 75-100 min; and the continuous heating and stirring time after the dropwise addition in S3 is 2.5-3.5 h.
[0011] Furthermore, the freeze drying is performed at -60 to -100°C for 15 to 25 hours.
[0012] Furthermore, the calcination is carried out in a tubular furnace with a protective gas atmosphere, heating to 250-350°C at 2-4°C / min, keeping the temperature for 45-75 minutes, then heating to 750-950°C at 3-8°C / min, keeping the temperature for 60-100 minutes, and cooling to room temperature at 3-8°C / min.
[0013] Furthermore, the protective gas includes nitrogen, argon or helium; and the protective gas introduction rate is 10-30 mL / min.
[0014] Technical theme 2: The present invention provides a method for preparing the nitrogen-oxygen co-doped carbon material as described in the first technical subject.
[0015] Technical Theme 3: The present invention provides an application of the nitrogen-oxygen co-doped carbon material as described in the first technical theme in the field of rubber waterstop reinforcing agent.
[0016] The beneficial effects of adopting the above technical solution are: 1. The present invention promotes the cross-linking of raw materials by adding a cross-linking agent and a hydrophilic polymer to obtain a macromolecular cross-linked product, thereby effectively improving the yield of the obtained reinforcing agent.
[0017] 2. The raw materials used in the present invention are cross-linked with each other and cooperate with each other to improve the degree of reaction and make the reaction more complete, thereby obtaining a carbon material with a more uniform particle size, which is beneficial to improving the reinforcement effect; at the same time, the macromolecular raw materials have a high degree of reaction and are mixed evenly, so that the nitrogen and oxygen atoms in the obtained carbon material reinforcing agent are evenly distributed, which is beneficial to the cross-linking between the reinforcing agent and the rubber, and is more conducive to exerting the reinforcement effect.
[0018] 3. The yield of the carbon material reinforcing agent obtained by the present invention is relatively high, and the yield can reach up to 32%, which exceeds the yield of conventional carbon material reinforcing agents; at the same time, the preparation scheme provided by the present invention has good yield stability, and the yield is maintained above 29%, and the difference between the yields is less than 3%. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a particle size distribution diagram of the nitrogen and oxygen co-doped carbon material obtained in Example 1 of the present invention; Figure 2 This is an XPS graph of oxygen element of the nitrogen-oxygen co-doped carbon material obtained in Example 1 of the present invention; Figure 3 This is the nitrogen element XPS graph of the nitrogen and oxygen co-doped carbon material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0020] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is clearly and completely described below in conjunction with specific embodiments.
[0021] Example 1 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 32%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 2-4 nm, the nitrogen atom content is 4.5 at%, and the oxygen atom content is 28.1 at%.
[0022] Example 2 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g maleamic acid in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 31.5%; the particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 1.8-5.1 nm, the nitrogen atom content is 3.8 at%, and the oxygen atom content is 19.7 at%.
[0023] Example 3 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g acrylamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen was passed at a rate of 20 mL / min, and heated to 300°C at 3°C / min, kept warm for 60 min, then heated to 850°C at 5°C / min, kept warm for 80 min, and finally cooled to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 31.0%; the obtained nitrogen-oxygen co-doped carbon material had a particle size distribution of 1.9-8.2 nm, a nitrogen atom content of 3.9 at%, and an oxygen atom content of 23.6 at%.
[0024] Example 4 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g propionamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 30.1%. The obtained nitrogen-oxygen co-doped carbon material has a particle size distribution of 2.4-7.7 nm, a nitrogen atom content of 3.7 at%, and an oxygen atom content of 25.1 at%.
[0025] Example 5 S1: Dissolve 6 g potassium aspartate, 2 g aminophylline and 3 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen was passed at a rate of 20 mL / min, and heated to 300°C at 3°C / min, kept warm for 60 min, then heated to 850°C at 5°C / min, kept warm for 80 min, and finally cooled to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 29.7%; the obtained nitrogen-oxygen co-doped carbon material had a particle size distribution of 4.4-12.0 nm, a nitrogen atom content of 4.0 at%, and an oxygen atom content of 29.3 at%.
[0026] Example 6 S1: Dissolve 10 g potassium aspartate, 4 g aminophylline and 8 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 30.3%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 4.1-11.5 nm, the nitrogen atom content is 3.6 at%, and the oxygen atom content is 28.5 at%.
[0027] Example 7 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of methoxy polyethylene glycol acrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 29.4%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 5.6-14.1 nm, the nitrogen atom content is 3.0 at%, and the oxygen atom content is 24.6 at%.
[0028] Example 8 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of polyethylene glycol diacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen was passed at a rate of 20 mL / min, and heated to 300°C at 3°C / min, kept warm for 60 min, then heated to 850°C at 5°C / min, kept warm for 80 min, and finally cooled to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 29.1%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material was 4.8-15.5 nm, the nitrogen atom content was 2.8 at%, and the oxygen atom content was 23.9 at%.
[0029] Example 9 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 5 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen was passed at a rate of 20 mL / min, and heated to 300°C at 3°C / min, kept warm for 60 min, then heated to 850°C at 5°C / min, kept warm for 80 min, and finally cooled to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 29.0%; the particle size distribution of the obtained nitrogen-oxygen co-doped carbon material was 7.1-18.7 nm, the nitrogen atom content was 2.1 at%, and the oxygen atom content was 19.4 at%.
[0030] Example 10 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 15 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen was passed at a rate of 20 mL / min, and heated to 300°C at 3°C / min, kept warm for 60 min, then heated to 850°C at 5°C / min, kept warm for 80 min, and finally cooled to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 31.1%; the obtained nitrogen-oxygen co-doped carbon material had a particle size distribution of 3.2-6.7 nm, a nitrogen atom content of 4.1 at%, and an oxygen atom content of 21.4 at%.
[0031] Embodiment 11 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 2.5 mL of emulsion A into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 29.6%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 4.8-9.2 nm, the nitrogen atom content is 3.1 at%, and the oxygen atom content is 20.5 at%.
[0032] Example 12 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3.5 mL of emulsion A into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 30.5%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 4.3-7.7 nm, the nitrogen atom content is 3.5 at%, and the oxygen atom content is 22.2 at%.
[0033] Embodiment 13 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 35 °C for 50 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 35 °C for 100 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min. After the addition is complete, heating and stirring are continued at 35°C for 3.5 h to obtain an intermediate product; S4: After freeze-drying the intermediate product at -60°C for 25 h, put it into a tubular furnace into which nitrogen was passed at a rate of 20 mL / min, and heated to 300°C at 3°C / min, kept warm for 60 min, then heated to 850°C at 5°C / min, kept warm for 80 min, and finally cooled to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material. The yield was 31.3%; the particle size distribution of the obtained nitrogen-oxygen co-doped carbon material was 3.3-6.5 nm, the nitrogen atom content was 3.6 at%, and the oxygen atom content was 19.2 at%.
[0034] Embodiment 14 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 45 °C for 30 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 45 °C for 75 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 45°C for 2.5 h after the addition is complete to obtain an intermediate product; S4: After freeze-drying the intermediate product at -100°C for 15 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 30.8%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 3.1-7.0 nm, the nitrogen atom content is 3.4 at%, and the oxygen atom content is 19.0 at%.
[0035] Embodiment 15 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which argon gas is passed at a rate of 10 mL / min, and heat it to 250°C at 2°C / min, keep it warm for 75 min, then heat it to 750°C at 3°C / min, keep it warm for 100 min, and finally cool it to room temperature at 3°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 29.7%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 3.0-8.1 nm, the nitrogen atom content is 3.8 at%, and the oxygen atom content is 19.3 at%.
[0036] Example 16 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which helium is passed at a rate of 30 mL / min, and the temperature is increased to 350°C at 4°C / min, kept warm for 45 minutes, then increased to 950°C at 8°C / min, kept warm for 60 minutes, and finally cooled to room temperature at 8°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 29.1%. The obtained nitrogen-oxygen co-doped carbon material has a particle size distribution of 2.5-6.6 nm, a nitrogen atom content of 2.9 at%, and an oxygen atom content of 16.4 at%.
[0037] Comparative Example 1 S1: Dissolve 8 g potassium aspartate, 3 g melamine and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 23.2%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 2.5-28.1 nm, the nitrogen atom content is 1.7 at%, and the oxygen atom content is 12.1 at%.
[0038] Comparative Example 2 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g sodium dodecyl sulfate in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen was passed at a rate of 20 mL / min, and heated to 300°C at 3°C / min, kept warm for 60 min, then heated to 850°C at 5°C / min, kept warm for 80 min, and finally cooled to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 19.4%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material was 5.7-33.5 nm, the nitrogen atom content was 1.1 at%, and the oxygen atom content was 13.8 at%.
[0039] Comparative Example 3 S1: Dissolve 8 g potassium aspartate and 3 g aminophylline in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 8.5%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 8.0-52.6 nm, the nitrogen atom content is 0.6 at%, and the oxygen atom content is 9.2 at%.
[0040] Comparative Example 4 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of polyvinyl alcohol in 10 mL of methanol, heat and stir at 40 °C for 85 min to obtain solution B; S3: heating and stirring solution B, while adding 3 mL of emulsion A dropwise into 1 mL of solution B at a rate of 5 mL / min, and heating and stirring at 40°C for 3 h after the addition is completed to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 13.3%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 7.4-31.5 nm, the nitrogen atom content is 1.3 at%, and the oxygen atom content is 11.0 at%.
[0041] Comparative Example 5 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water and stir at room temperature for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 10 mL of methanol and stir at room temperature for 85 min to obtain solution B; S3: Stir solution B at room temperature, and at the same time, drop 3 mL of emulsion A into 1 mL of solution B at a rate of 5 mL / min. After the addition is completed, continue stirring at room temperature for 3 h to obtain an intermediate product; S4: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 15.4%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 9.0-32.6 nm, the nitrogen atom content is 1.0 at%, and the oxygen atom content is 10.2 at%.
[0042] Comparative Example 6 S1: Dissolve 8 g potassium aspartate, 3 g aminophylline and 5 g crotonamide in 50 mL deionized water, heat and stir at 40 °C for 40 min to obtain emulsion A; S2: Dissolve 1 g of triethylene glycol dimethacrylate in 3 mL of emulsion A, and continue heating and stirring at 40 °C for 3 h to obtain an intermediate product; S3: After freeze-drying the intermediate product at -80°C for 20 h, put it into a tubular furnace into which nitrogen is passed at a rate of 20 mL / min, and heat it to 300°C at 3°C / min, keep it warm for 60 min, then heat it to 850°C at 5°C / min, keep it warm for 80 min, and finally cool it to room temperature at 5°C / min to obtain nitrogen-oxygen co-doped carbon material with a yield of 9.1%. The particle size distribution of the obtained nitrogen-oxygen co-doped carbon material is 8.3-41.2 nm, the nitrogen atom content is 0.7 at%, and the oxygen atom content is 9.5 at%.
[0043] Embodiment 17 100 parts of natural rubber, 30 parts of reinforcing agent (nitrogen and oxygen co-doped carbon material obtained in Example 1), 6 parts of activator (zinc oxide), 1 part of stearic acid, 17 parts of softener (petroleum resin), 3 parts of antioxidant (MB), 2 parts of accelerator (CZ), 25 parts of filler (FD170, Guangzhou Dongxin Chemical Co., Ltd.) and 16 parts of vulcanizing agent (sulfur).
[0044] S1: Plasticizing Set the initial temperature of the internal mixer to 70℃ and the speed to 40 rpm, cut the natural rubber into small pieces and add them into the internal mixer, plasticate for 6 minutes, and discharge when the temperature of the internal mixer reaches 100℃. Pass it on the open mixer, make triangle bags 4 times, and leave it for at least 8 hours before use.
[0045] S2: One-stage mixing Set the initial temperature of the internal mixer to 85℃ and the speed to 35 rpm. Add the plasticized natural rubber to the internal mixer. After about 45 seconds, lift the top plug to add reinforcing agent, filler, activator, stearic acid, softener and antioxidant, press the top plug, mix for 160 seconds, lift the plug once in the middle, and discharge the rubber at a temperature of 110℃. After a section of mixed rubber falls into the open mixer, adjust the roller distance to 5mm, automatically pour the rubber 4 times, and the roller temperature of the open mixer does not exceed 60℃. After pouring the rubber, unload the sheet and leave it for at least 8 hours before use.
[0046] S3: Second stage mixing Set the initial temperature of the internal mixer to 85°C and the speed to 35 rpm. Fill the first-stage mixed rubber into the internal mixer. After pressurizing for 45 seconds, lift the top plug to add the vulcanizer and accelerator. Press the top plug, mix for 80 seconds, and the mixing temperature is 110°C, and discharge the rubber. After the second-stage mixed rubber falls into the open mixer, adjust the roller distance to 5mm, and automatically pour the rubber 4 times. The roller temperature of the open mixer does not exceed 60°C. After the pouring is completed, remove the sheet and park it for at least 8 hours before use to obtain sample 1.
[0047] Embodiment 18 The preparation method is the same as Example 17, the only difference is that the carbon material used is the one obtained in Example 2, and Sample 2 is obtained.
[0048] Embodiment 19 The preparation method is the same as Example 17, the only difference is that the carbon material used is the one obtained in Example 3, and Sample 3 is obtained.
[0049] Embodiment 20 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 4, and Sample 4 is obtained.
[0050] Embodiment 21 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 5, and Sample 5 is obtained.
[0051] Embodiment 22 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 6, and Sample 6 is obtained.
[0052] Embodiment 23 The preparation method is the same as Example 17, the only difference is that the carbon material used is the one obtained in Example 7, and Sample 7 is obtained.
[0053] Embodiment 24 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 8, and Sample 8 is obtained.
[0054] Embodiment 25 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 9, and Sample 9 is obtained.
[0055] Embodiment 26 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 10, and sample 10 is obtained.
[0056] Embodiment 27 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 11, and sample 11 is obtained.
[0057] Embodiment 28 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 12, and sample 12 is obtained.
[0058] Embodiment 29 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 13, and sample 13 is obtained.
[0059] Embodiment 30 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 14, and sample 14 is obtained.
[0060] Embodiment 31 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 15, and sample 15 is obtained.
[0061] Embodiment 32 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Example 16, and sample 16 is obtained.
[0062] Embodiment 33 The preparation method is the same as Example 17, the only difference is that the carbon material used is the one obtained in Comparative Example 1, and Sample 17 is obtained.
[0063] Embodiment 34 The preparation method is the same as Example 17, the only difference is that the carbon material used is the one obtained in Comparative Example 2, and Sample 18 is obtained.
[0064] Embodiment 35 The preparation method is the same as Example 17, the only difference is that the carbon material used is the one obtained in Comparative Example 3, and Sample 19 is obtained.
[0065] Embodiment 36 The preparation method is the same as Example 17, the only difference being that the carbon material used is the one obtained in Comparative Example 4, and Sample 20 is obtained.
[0066] Embodiment 37 The preparation method is the same as Example 17, the only difference is that the carbon material used is the one obtained in Comparative Example 5, and Sample 21 is obtained.
[0067] Embodiment 38 The preparation method is the same as Example 17, the only difference is that the carbon material used is obtained from Comparative Example 6, and Sample 22 is obtained.
[0068] Effect example 1: Rubber waterstop performance test According to Q / CR 562.2-2017 “Railway Tunnel Drainage Materials Part 2: Waterstop”, performance tests were conducted on samples 1 to 22, and the results are shown in Table 1.
[0069] Table 1 Performance of Samples 1 to 22
[0070] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art may still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A nitrogen-oxygen co-doped carbon material, characterized in that: The preparation method is as follows: S1: dissolving potassium aspartate, aminophylline and a hydrophilic polymer in deionized water, heating and stirring to obtain an emulsion A; S2: dissolving the cross-linking agent in methanol, heating and stirring to obtain solution B; S3: heating and stirring solution B, while adding emulsion A dropwise into solution B, and continuing heating and stirring after the addition is complete to obtain an intermediate product; S4: freeze-drying the obtained intermediate product and then calcining it to obtain a nitrogen-oxygen co-doped carbon material; The hydrophilic polymer includes crotonamide, maleamic acid, acrylamide or propionamide; The cross-linking agent includes triethylene glycol dimethacrylate, polyethylene glycol diacrylate or methoxy polyethylene glycol acrylate.
2. The nitrogen-oxygen co-doped carbon material according to claim 1, characterized in that: The mass ratio of potassium aspartate, aminophylline, hydrophilic polymer and cross-linking agent is 6-10:2-4:3-8:1.4-2.
3. The nitrogen-oxygen co-doped carbon material according to claim 1, characterized in that: The ratio of the cross-linking agent to methanol is 1 g: 5-15 mL.
4. The nitrogen-oxygen co-doped carbon material according to claim 1, characterized in that: The volume ratio of the emulsion A to the solution B is 2.5-3.5:
1.
5. The nitrogen-oxygen co-doped carbon material according to claim 1, characterized in that: The heating and stirring temperature is 35-45°C; the heating and stirring time in S1 is 30-50 min; the heating and stirring time in S2 is 75-100 min; and the continuous heating and stirring time after the dropwise addition in S3 is 2.5-3.5 h.
6. The nitrogen-oxygen co-doped carbon material according to claim 1, characterized in that: The freeze drying is performed at -60 to -100°C for 15 to 25 hours.
7. The nitrogen-oxygen co-doped carbon material according to claim 1, characterized in that: The calcination is carried out in a tubular furnace with a protective gas atmosphere, heating to 250-350° C. at 2-4° C. / min, keeping the temperature for 45-75 minutes, then heating to 750-950° C. at 3-8° C. / min, keeping the temperature for 60-100 minutes, and cooling to room temperature at 3-8° C. / min.
8. The nitrogen-oxygen co-doped carbon material according to claim 7, characterized in that: The protective gas includes nitrogen, argon or helium; the protective gas introduction rate is 10-30 mL / min.
9. A method for preparing the nitrogen-oxygen co-doped carbon material as claimed in any one of claims 1 to 8.
10. Use of the nitrogen-oxygen co-doped carbon material as claimed in any one of claims 1 to 8 in the field of rubber waterstop reinforcement agents.
Citation Information
Patent Citations
Preparation method of hierarchical pore nitrogen-oxygen-doped carbon super capacitor electrode material
CN107910200A
Preparation method of oxygen, nitrogen and metal co-doped carbon material and application of oxygen, nitrogen and metal co-doped carbon material in rubber
CN115583647A
Preparation method and application of nitrogen-oxygen co-doped nano-porous carbon material
CN118616006A
Preparation method and application of oxygen-sulfur doped porous carbon material for rubber waterstop reinforcing agent
CN118954485A
Preparation method of heteroatom doped carbon from amino acid as a precursor
KR1020120122204A